2016
DOI: 10.1016/j.cct.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness of concise cognitive behavioral therapy with or without pharmacotherapy for depressive and anxiety disorders; a pragmatic randomized controlled equivalence trial in clinical practice

Abstract: . (2016). The clinical effectiveness of concise cognitive behavioral therapy with or without pharmacotherapy for depressive and anxiety disorders; a pragmatic randomized controlled equivalence trial in clinical practice. Contemporary Clinical Trials, 47 131-138. See next page for additional authorsThe clinical effectiveness of concise cognitive behavioral therapy with or without pharmacotherapy for depressive and anxiety disorders; a pragmatic randomized controlled equivalence trial in clinical practice Abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
2
7
0
2
Order By: Relevance
“…This result is con-gruent with those of Meuldijk et al (30). During initial sessions of therapy, it was observed that there was a reciprocal relation between anger and some parts of anxiety in the participants of this study, leading to a vicious circle; which meant that participants could not express their anger in an appropriate, sensible way probably due to a hidden social anxiety that prevents them from expression of anger.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is con-gruent with those of Meuldijk et al (30). During initial sessions of therapy, it was observed that there was a reciprocal relation between anger and some parts of anxiety in the participants of this study, leading to a vicious circle; which meant that participants could not express their anger in an appropriate, sensible way probably due to a hidden social anxiety that prevents them from expression of anger.…”
Section: Discussionsupporting
confidence: 91%
“…There was a significant difference in the mean scores of general health between the experimental and control groups in the post-test and follow-up. This result is congruent with those of Meuldijk et al (30). General health is a construct that can be evaluated based on physical and psychological conditions of individuals including psychological distress (anxiety, depression, etc.…”
Section: Discussionsupporting
confidence: 89%
“…However, there is a trend toward designing concise treatments for mental health problems, which can be provided via the Internet and are thought to be more cost-effective. An RCT that compared the effectiveness of concise CBT with standard CBT for depression and anxiety found that they were equivalent [ 103 ]. Most previous meta-analyses that have investigated the effectiveness of psychological interventions for depression or anxiety have also found no differences between treatments with a short or long duration [ 14 , 95 , 97 , 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Leunen et al, (2017) (11) studies with a duration of treatment ranging from 12-18 hours have a more significant effect than the length of short or longer treatments. However, an RCT that compared the effectiveness of a concise CBT and standard CBT in PLWH with depression and anxiety showed similar effectiveness (64). Several meta-analyses that investigated the efficacy of psychological interventions for depression and anxiety for PLWH also found no difference between short or long duration treatments (29)(30)63).…”
Section: Discussionmentioning
confidence: 98%